Denunziation als soziale Praxis : Fälle aus der NS-Militärjustiz - Hornung-Ichikawa, Ela 1959- (Böhlau, 2010)
Denunciations were an essential component of everyday life under Nazism and affected almost every aspect of life. During the war, denunciations became a mass phenomenon. In Austria the subject was noticed relatively late. The attention proceeds from a general definition of terms, to a specific interpretation on the basis of archive sources (Wehrmacht legal records) and then to individual case reconstructions on the basis of oral history interviews, that is to say, from a macro to a micro perspective.The closed holding relates to charges on the offence of Wehrkraftzersetzung (subversion of the armed forces), most of which were reported by former residents in the Ostmark at the central court, Vienna, in 1943-1945. Central to this are above all questions of social history and the history of mentality, such as the significance of social milieu (denunciation as “release” from class or interest differences, as a group phenomenon, etc.), and of gender (gender-differentiated behaviour, denunciation as “release” from conflicts concerning gender hierarchy), of generation, of political/ideological orientation, and of the significance of the social environment, the sphere of life and the locality. Of interest, however, are not just the historical conditions under the Nazi regime, but also the room for manoeuvre of men and women - in the military milíeu in the endphase of the war - and the communicative mechanisms that led to political denunciation